Family planning among women with unmet need contraception: a scoping review - Resya Aprillia; Andari Wuri Astuti; Anjarwati Anjarwati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Maternal health is a topical issue of Population, Family Planning, and Family Development Programs in the 2030 SDGs indicators, namely by ensuring universal access to sexual health and reproductive rights. The Unmet need contraception is one of the main barriers to achieving SDGs goals in low-and middle-income countries. This study aims to explore and map the scientific evidence related to family planning in women of childbearing age with Unmet need contraception. Scoping review refers to the framework of Arksey O'Malley and is documented based on the PRISMA-ScR Checklist guide. Article search using 3 databases Pubmed, Sciencedirect, Ebsco host and 1 Gray literature Google Scholar by filtering the year of publication from 2019-2022. Obtained 15 articles are eligible and 3 findings of the theme are socio-demographic aspects, socio-psychology, and health. The results of the review found that the motivation of women of childbearing age in deciding Unmet need contraception is to exclude children and limit the number of children. Women of childbearing age with low decision-making autonomy within a family are most influential in determining the Unmet need contraception. Planning related to contraceptive use in the future is expressed by the motivation of contraceptive use plans at one time. Abstrak: Kesehatan ibu menjadi Isu Topik Program Kependudukan, Keluarga Berencana dan Pembangunan Keluarga dalam Indikator SDGs 2030 yaitu dengan menjamin akses universal terhadap kesehatan seksual dan hak reproduksi. Unmet need kontrasepsi merupakan salah satu hambatan utama dalam mencapai tujuan SDGs di negara berpenghasilan rendah dan menengah. Penelitian ini bertujuan untuk menggali dan memetakan bukti ilmiah terkait dengan perencanaan keluarga pada Wanita Usia Subur dengan Unmet need kontrasepsi. Scoping review ini mengacu pada Framework dari Arksey O’Malley dan didokumentasikan berdasarkan panduan PRISMA-ScR Checklist. Pencarian artikel menggunakan 3 Database Pubmed, Sciencedirect, Ebsco host serta 1 Grey literature Google Scholar dengan memfilter tahun terbit artikel sejak 2019-2022. Didapatkan 15 artikel yang eligible serta 3 Temuan tema yaitu Aspek Sosio-Demografic, Sosio-Psikologi, dan Kesehatan. Hasil review didapatkan bahwa motivasi wanita usia subur dalam memutuskan Unmet need kontrasepsi yaitu untuk menjarangkan anak dan untuk membatasi jumlah anak. Wanita usia subur dengan otonomi pengambilan keputusan yang rendah didalam suatu keluarga paling berpengaruh terhadap penentuan Unmet need kontrasepsi. Perencanaan terkait dengan penggunaan kontrasepsi dimasa depan dinyatakan dengan adanya motivasi rencana penggunaan kontrasepsi disuatu waktu.